Opinions of Japanese and American ALS caregivers regarding tracheostomy with invasive ventilation (TIV). Issue 1 (17th February 2016) - Christodoulou, Georgia; Goetz, Raymond; Ogino, Mieko; Mitsumoto, Hiroshi; Rabkin, Judith
Abstract : Our objective was to learn more about possible factors contributing to the higher rates of tracheostomy with invasive ventilation (TIV) for ALS patients in Japan compared with the United States by eliciting attitudes of caregivers of ALS patients in both countries. One hundred and fifty-four American caregivers from five, geographically-distributed ALS clinics and 66 Japanese caregivers from six sites in Japan completed questionnaires regarding TIV. Results showed that 33% of American caregivers were in favor of TIV for their family member compared to 53% of Japanese caregivers; 44% of American and 37% of Japanese caregivers were undecided; and 22% of American and 10% of Japanese caregivers were opposed ( p <.01). Within patient-caregiver dyads, agreement in the American sample was fair, while the Japanese dyads showed poor agreement. Maintaining quality of life and patients reaching a milestone were the most common reasons for favoring TIV in the American and Japanese samples, respectively. Reasons for opposing TIV did not significantly differ. Findings suggest that caregiver preferences may influence actual choices for ALS patients. More frequent endorsement of TIV by Japanese vs. American caregivers is consistent with higher rates of TIV among Japanese patients. The results reflect the importance of caregivers' opinions in patient care.